BURMA DAN PERJUANGAN DEMOKRASI, ANALISIS ISI FILM THE LADY - Nurul Ichsani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2016)
Film was born a great idea to bridge communication by combining two language reality containing historical existence. By utilizing content analysis introduced by Ole Holsty involving tow coder, this study aims to analyze percentage of the representation of struggle for democracy on The Lady film and to prove whether The Lady film represents woman as main figure for Burmese democracy. This study suggests that struggle for democracy in The Lady film is dominated by popular support which becomes a bedrock for The Lady script. This also suggests that ideology inception on struggle rooted from the power of